2019
DOI: 10.1088/1361-6528/ab0ed8
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the efficiency of energy harvesting from salt gradient with ion-selective nanochannel

Abstract: The development of nanofluidic energy harvesting system plays a fundamental role in harvesting osmotic power from Gibbs free energy within salt concentration gradient, which is considered as a future clean and renewable energy source. In this study, a silica-nanochannel based nanofluidic energy harvesting system was fabricated and its output power density could reach 705 W/m 2 under suitable KCl concentration bias which exceeded-by almost two orders of magnitude-the results obtained by previous work. The enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…hydrogel [ 25 ]). Although these works have made progress in fundamental study and provide theoretical guidance for selective membranes in osmotic power conversion, the advance of materials is hindered by complicated preparation and inadequate mechanical properties, limiting large-scale use of SGP generation [ 22 , 26 , 27 ]. Therefore, there is a need to construct membranes with desirable performance and facile synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…hydrogel [ 25 ]). Although these works have made progress in fundamental study and provide theoretical guidance for selective membranes in osmotic power conversion, the advance of materials is hindered by complicated preparation and inadequate mechanical properties, limiting large-scale use of SGP generation [ 22 , 26 , 27 ]. Therefore, there is a need to construct membranes with desirable performance and facile synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-electroporation uses 90 nm wide channels for precise dose control for the injection of nanoparticles, plasmids and siRNA on a single cell basis and demonstrate the improvement of the process when channels in the submicron regime are used 47 . A nanofluidic power generator device of a power density of 705 W/m 2 using a KCl concentration gradient in a nanochannel of the dimensions 715 nm × 350 nm × 40 nm was demonstrated by Zhang et al 48 —fabricated in a silicon chip. However, care must be taken when comparing softlithography devices with silicon applications.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of the channel length is considered to produce an increment in I osm (R c diminution) with a loss of selectivity (E m diminution), setting another trade-off situation. 126,127,[189][190][191][192] To shed light on this problem, Cao et al conducted a comprehensive analysis of the impact of the channel length on the energyconversion performance. 193 Employing PNP simulations, the authors found that the trade-off between the increment of I osm and the decrease of E m resulted in an enhancement of the output power at low and moderate concentration gradient (<300-fold) as the channel length decreases.…”
Section: Channel Lengthmentioning
confidence: 99%
“…On the other hand, if the electrolyte concentration in the diluted reservoir is excessively low, a similar detriment in the output power can occur due to the diminution of t + , but in this case, this effect is attributed to the diminution in the surface charge caused by the regulation charge effect at low electrolyte concentration. 190,213,214 For asymmetric channels, also the directionality of the gradient is important; i.e. at which side of the nanoporous membrane the highly concentrated and diluted solutions are placed (Fig.…”
Section: Concentration Gradientmentioning
confidence: 99%